Laser material interactions in tamped materials on picosecond time scales in aluminum - Parsons, Sophie E.; Turner, Ross E.; Armstrong, Michael R.; Radousky, Harry B.; Garay, Javier E.; Beg, Farhat N. (Applied physics letters, 2023)
A 100 ps laser is used to probe the pressure generation, depth of the non-solid ablator, and the non-linear optical effects through tamper materials. Samples consisted of an aluminum ablator with tampers of sapphire and coverslip glass. In general, the sapphire tamped sample achieves higher pressures at lower laser intensities as compared to the coverslip glass tamped sample. Attempts to model the details of this set of experimental data with standard available radiation coupled hydrodynamic codes make clear that more physics is needed in these simulations to accurately predict the impact of the tamper material on the pressure generation and the depth of non-solid aluminum.